Criminological typology of radical criminals among sentenced to imprisonment - P. Yu. Danylchenko (Law and Safety)
The article is devoted to the study of radical criminals among those sentenced to imprisonment. The purpose of the article is to provide a criminological typological characteristic of criminal radicals among those sentenced to imprisonment. The following tasks have been solved to achieve this goal: 1) to define the typological criteria for the division of criminal radicals among those sentenced to imprisonment; 2) to identify the relevant criminological types according to the criteria; 3) to identify and describe the signs of criminological types of criminal radicals among those sentenced to imprisonment.